Analysis of Green Finance, Green Innovative Behavior and Digitization of Sustainable Competitive Advantage Mediated by Pro-Environmental Behavior in MSME Actors in West Nusa Tenggara Province - huda, Nurul; Mongid, Abdul (Program Studi Akuntansi Universitas Islam Lamongan, 2025)
This research aims to analyze the influence of Green Finance, Green Innovative Behavior, and Digitization on the Sustainable Competitive Advantage of MSMEs in West Nusa Tenggara Province, with Pro-Environmental Behavior as a mediating variable. This research uses a quantitative approach with an explanatory research type, involving 150 MSME actors selected through purposive sampling. Data was collected through questionnaires and analyzed using the Structural Equation Modeling (SEM) model based on Partial Least Squares (PLS). The research results show that the three independent variables directly have a significant effect on Sustainable Competitive Advantage. Apart from that, Pro-Environmental Behavior is proven to mediate the influence of Green Finance, Green Innovative Behavior, and Digitization on these advantages. These findings emphasize the importance of integrating green and digital strategies supported by environmentally friendly behavior in building sustainable competitiveness of MSMEs in the digital era.